Three Proteins (Hpa2, HrpF and XopN) Are Concomitant Type III Translocators in Bacterial Blight Pathogen of Rice - Mo, Xuyan; Zhang, Liyuan; Liu, Yan; Wang, Xuan; Bai, Jiaqi; Lu, Kai; Zou, Shenshen; Dong, Hansong; Chen, Lei (Frontiers in Microbiology, 2020)
Type III (T3) proteic effectors occupy most of the virulence determinants in eukaryote-pathogenic Gram-negative bacteria. During infection, bacteria may deploy a nanomachinery called translocon to deliver T3 effectors into host cells, wherein the effectors fulfil their pathological functions. T3 translocon is hypothetically assembled by bacterial translocators, which have been identified as one hydrophilic and two hydrophobic proteins in animal-pathogenic bacteria but remain unclear in plant pathogens. Now we characterize Hpa2, HrpF, and XopN proteins as concomitant T3 translocators in rice bacterial blight pathogen by analyzing pathological consequences of single, double and triple gene knockout or genetic complementation. Based on these genetic analyses, Hpa2, HrpF, and XopN accordingly contribute to 46.9%, 60.3%, and 69.8% proportions of bacterial virulence on a susceptible rice variety. Virulence performances of Hpa2, HrpF and XopN were attributed to their functions in essentially mediating from-bacteria-into-rice-cell translocation of PthXo1, the bacterial T3 effector characteristic of transcription factors targeting plant genes. On average, 61%, 62%, and 71% of PthXo1 translocation are provided correspondingly by Hpa2, HrpF, and XopN, while they cooperate to support PthXo1 translocation at a greater-than-95% extent. As a result, rice disease-susceptibility gene SWEET11, which is the regulatory target of PthXo1, is activated to confer bacterial virulence and induce the leaf blight disease in rice. Furthermore, the three translocators also undergo translocation, but only XopN is highly translocated to suppress rice defense responses, suggesting that different components of a T3 translocon deploy distinct virulence mechanisms in addition to the common function in mediating bacterial effector translocation.